2021
DOI: 10.1139/tcsme-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tool pin profile on the hook geometry and mechanical properties of a friction stir spot welded AA6082-T6 aluminum alloy

Abstract: AA6082-T6 alloy was joined by friction stir spot welding using five different pin profiles, such as a cylindrical, conical, triangular, hexagonal and cylindrical with two grooves, at different dwell time. The joints welded by cylindrical pins had larger effective weld width. But, grooves on the cylindrical pin decreased the effective weld width. The hook was bent downward from the interface of the sheets in the weld made with hexagonal pin, which had the smallest effective weld width. When conical pin was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…In addition, they contain comparatively coarse (Fe, Mn) 3 SiAl l2 intermetallic and low-density fine dispersed Mg 2 Si precipitates. These microstructure features are consistent with that reported in other works [ 2 , 36 , 47 ]. It can be observed also that the AA 6082-T6 sheets of 1 ( Figure 11 a) and 2 mm ( Figure 11 b) thickness have average grain sizes of 11 ± 2 and 17 ± 1.5 μm, respectively.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, they contain comparatively coarse (Fe, Mn) 3 SiAl l2 intermetallic and low-density fine dispersed Mg 2 Si precipitates. These microstructure features are consistent with that reported in other works [ 2 , 36 , 47 ]. It can be observed also that the AA 6082-T6 sheets of 1 ( Figure 11 a) and 2 mm ( Figure 11 b) thickness have average grain sizes of 11 ± 2 and 17 ± 1.5 μm, respectively.…”
Section: Resultssupporting
confidence: 93%
“…In addition, they contain comparatively coarse (Fe, Mn)3SiAll2 intermetallic and low-density fine dispersed Mg2Si precipitates. These microstructure features are consistent with that reported in other works [2,36,47]. It can be observed also that the AA 6082-T6 sheets of 1 (Figure 11a) and 2 mm (Figure 11b) (a-d) the FSSW lap joints of AA6082-T6 welded at a constant dwell time of 3 s and different rotational speeds of 400 to 1000 rpm [36] and (e-h) RFSSW deposited at a 400 rpm rotation speed and a 1 mm/min deposition rate.…”
Section: Microstructure Investigation Of the Base Materialssupporting
confidence: 93%
See 1 more Smart Citation
“…During the dwell time, the tool shoulder penetrates the top surface of the upper layer and the tool pin penetrates the top surface of the lower layer. This action supplies the driving power required for the upward movement of the materials in the lower layer as shown in Figure 6 b. Aydin et al [ 41 ] and Ji et al [ 42 ] reported similar outcomes. In addition, the creation of the kissing bond is due to the inadequate flow caused by the pin’s incomplete stirring.…”
Section: Resultsmentioning
confidence: 66%
“…This was due to increased heat input, which results in effective material plasticization. This could be linked to the hardening precipitates becoming coarser due to the increased heat input, resulting in a higher hardness value [35]. Fine‐grain development strengthens grain boundaries by preventing dislocation motion during hardness indentation.…”
Section: Resultsmentioning
confidence: 99%